Engineering Enhanced Vaccine Cell Lines To Eradicate Vaccine-Preventable Diseases: the Polio End Game - van der Sanden, Sabine M. G. (J Virol, 2016)
Vaccine manufacturing costs prevent a significant portion of the world's population from accessing protection from vaccine-preventable diseases. To enhance vaccine production at reduced costs, a genome-wide RNA interference (RNAi) screen was performed to identify gene knockdown events that enhanced poliovirus replication. Primary screen hits were validated in a Vero vaccine manufacturing cell line using attenuated and wild-type poliovirus strains. Multiple single and dual gene silencing events increased poliovirus titers >20-fold and >50-fold, respectively. Host gene knockdown events did not affect virus antigenicity, and clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9-mediated knockout of the top candidates dramatically improved viral vaccine strain production. Interestingly, silencing of several genes that enhanced poliovirus replication also enhanced replication of enterovirus 71, a clinically relevant virus to which vaccines are being targeted. The discovery that host gene modulation can markedly increase virus vaccine production dramatically alters mammalian cell-based vaccine manufacturing possibilities and should facilitate polio eradication using the inactivated poliovirus vaccine. IMPORTANCE Using a genome-wide RNAi screen, a collection of host virus resistance genes was identified that, upon silencing, increased poliovirus and enterovirus 71 production by from 10-fold to >50-fold in a Vero vaccine manufacturing cell line. This report provides novel insights into enterovirus-host interactions and describes an approach to developing the next generation of vaccine manufacturing through engineered vaccine cell lines. The results show that specific gene silencing and knockout events can enhance viral titers of both attenuated (Sabin strain) and wild-type polioviruses, a finding that should greatly facilitate global implementation of inactivated polio vaccine as well as further reduce costs for live-attenuated oral polio vaccines. This work describes a platform-enabling technology applicable to most vaccine-preventable diseases.